Factors affecting implementation of tuberculosis contact investigation and tuberculosis preventive therapy among children in Sabah, East Malaysia: A qualitative study - Michelle May D. Goroh; Christel H. A. Van Den Boogaard; Khamisah Awang Lukman; Christopher Lowbridge; Wong Ke Juin; Timothy William; Mohammad Saffree Jeffree; Anna P. Ralph (Plos One, 2023)
Contact investigation and TB preventive treatment of children under five years of age who are close contacts of a TB case is a key component of TB prevention. However, the uptake of TB preventive treatment is low in many high-TB burden settings. This study explores factors affecting the implementation of TB contact investigation and preventive treatment among children in Malaysia’s city of Kota Kinabalu, Sabah State. This study was conducted in three primary health clinics between 2019 and 2020. We purposively sampled 34 parents and guardians of child contacts eligible for TB preventive treatment, and 25 healthcare providers involved in the management of child contacts. We conducted thematic analysis of semi-structured interviews and focus group discussions to illicit factors affecting implementation and uptake of TB contact investigation and TB preventive therapy. Six main themes emerged from the analyses–four of these relating to contact investigation and two relating to TB preventive therapy. Factors affecting TB contact investigation were addressed under system related factors (external factors, stakeholder collaboration, healthcare workers’ and clients’ concerns), clinic related factors (perceived performance, clinic schedule, and space), healthcare worker related factors (cooperation, commitment, knowledge, misconception, counselling and communication) and patient and contact related factors (cooperation and commitment). Factors affecting TB preventive treatment delivery were addressed under guardian related factors (cooperation, commitment, knowledge and misconception) and treatment related factors (child-friendly form and adverse effects). To address gaps and barriers identified in our study, we recommend developing system capacity to maintain routine contact investigation and preventive treatment in the context of external program risks, providing training to healthcare workers to address misconceptions, safeguarding vulnerable clients against the risk of detention and deportation while accessing care, ensuring public and private services are provided regardless of migration status, and improving processes and resources for contact investigation and preventive treatment.